Teenagers’ self-evaluation features in the ATO zone living conditions - Shalnyeva, Pauline (Bulletin of Taras Shevchenko National University of Kyiv. Psychology, 2017)
In this article we review the problems of selfevaluation in the stress conditions, especially living in the zone of antiterrorist operation, and the features of the selection the certain psychologic defence mechanisms and coping strategies. There were identified two factors of stress resistance and one factors of triggers of the stress.